Project-based Learning Integrated Padlet and Motivation on Students’ Writing Skill - Lubis, Sofia Idawati; Prihartini, Syafrina (Jurnal Pedagogi dan Pembelajaran, 2024)
One of the most effective strategies in facing the challenges of this digital age is to integrate technology into Project-based Learning (PjBL) in English classrooms. Teacher innovation and creativity are expected to improve students' competence in English, especially in writing This study aims to analyze the effect of a project-based learning model integrated Padlet and motivation on students' writing skills. This research method is post-test-only experimental research with a 2x2 factorial design.  The population is grade VIII students at junior high school. Samples of 2 classes were selected using cluster random sampling and divided into two groups; that is, the experimental group and the control group. The instruments used were motivation questionnaires and writing tests. Data were analyzed with a two-way ANOVA and Tuckey test. The results proved that, first, there was a significant difference in the students’ writing competence between the students who were taught with PjBL-integrated Padlet and students who were taught conventionally. Second, there was a significant interactional effect on students' writing competence between the learning model applied and student motivation. Third, there was a significant difference in the students’ writing competence between the students who had high motivation when they were taught with PjBL-integrated Padlet and the conventional model. Fourth, there was a significant difference in the students’ writing competence between the students who had low motivation when they were taught with PjBL-integrated Padlet and the conventional model.